Diagnostic value of alpha-fetoprotein and lens culinaris agglutinin-reactive Alpha-fetoprotein in liver cirrhosis and hepatocellular carcinoma patients in Pakistan - Rauf, Anum (International Journal of Pathology, 2024)
Background: Hepatocellular carcinoma (HCC) is the most commonly encountered liver cancer. Because of latent HCV infections, there is projected rise in new HCC cases in Pakistan; with the onset of HCC several decades after initial infection has occurred. As it is diagnosed at very late stage, predicted outcome of HCC is poor. This results in effective medical intervention difficult. The purpose of this study is to establish a serum marker and/or panels of serum markers, that can detect the at risk patients with chronic liver disease, not only before but also after early development of HCC. Methods: This study was conducted for ten months in Lahore General Hospital, Lahore, Punjab, Pakistan after taking the approval from the ethical board. A total of eighty patients (40 patients of HCC and 40 patients of Liver cirrhosis) were included using non-probability, consecutive sampling. AFP and AFP-L3 levels of these patients were measured. The data was analyzed using SPSS Ver. 25. A p-value of ≤0.05 was considered as statistically significant. Results: In group 1, the mean age of patients was 60.02 ± 11.5 years and in group 2, it was 60.80 ± 7.42 years. In group 1, the mean of AFP was 64.93 ± 171.76 (ng/mL) and AFP-L3 was 0.56 ± 0.51(ng/mL). On the other hand, in group 2, the mean of AFP was 329.88 ± 231.55 (ng/mL) and AFP-L3 was 177.59 ± 104.10 (ng/mL). Significant association was found between AFP and AFP-L3 in both groups. Receiver operating characteristic (ROC) curve for AFP and AFP-L3 in relation to both groups obtained. The sensitivity of AFP was 85% and specificity was 80%. The sensitivity and specificity of AFP-L3 was 90 and 100%, respectively. Conclusion: AFP-L3 has a better diagnostic value for Hepatocellular carcinoma than AFP